A Tribute to Judge Barry S. Schermer: Judge, Teacher, Friend & the Lessons Learned - Sandra F. Louis (Washington University Journal of Law & Policy, 2017)
This Article recounts the many lessons shared by those who have studied and worked under Judge Barry Schermer. Louis revisits her time as a former clerk and the recent anecdotes shared at a symposium in honor of Judge Schermer’s thirty years of services as a bankruptcy judge, summarizing the professional skills they all learned. The author also includes the practical lessons she learned under Judge Schermer, with subjects including travel, food, and enjoying the process.
Keywords: Washington University School of Law; Clerkship; Federal Clerkship; Mentorship; Judge Schermer